Frequent peritoneal dialysis-related peritonitis:clinical characteristics and risk factors - XU Li; WANG Yan; FANG Yuan; ZHAO Chen; CHU Zhao-xia; REN Wei (Linchuang shenzangbing zazhi)
Objective To identify the clinical characteristics and factors of frequent peritoneal dialysis(PD)-related peritonitis.Methods A retrospective study was conducted on patients undergoing continuous ambulatory peritoneal dialysis following PD catheterization from January 2007 to December 2014 in Anhui Province Hospital The frequent PD-related peritonitis was defined by two or more onsets in one year,and the patients with only one onset served as the control group.The clinical and laboratory data of the two groups were compared and the risk factors of frequent PD-related peritonitis were analyzed.Results There were 13 cases with infectious peritonitis of 30 cases/times in frequent group,and 57 cases with infectious peritonitis of 57 cases/times in the control group.As compared with those in the control group,the patients with frequent peritonitis had higher significantly blood pressure(P = 0.042) and body mass index(BMI)(P = 0.009),but lower hemoglobin(P =0.007) and plasma albumin(P = 0.003),with higher intact parathyroid hormone(P<0.05),gramnegative bacteria(33.33%) and fungal infection rates(10.00%),of which the increasing trend of gram-negative bacteria was more obvious(P = 0.035).Moreover,the patients without timely treatment[7 cases(53.85%) vs.13 cases(22.81%),P<0.05]and adequate anti-infection course[5 cases(38.46%) vs. 8 cases(14.04%),P<0.05]increased.No differences were found between the two group in age,gender,dialysis age,education,inducing factors of peritonitis,mortality,residual renal function,peripheral blood leukocytes,calcium,phosphorus,C-reactive protein,total cholesterol,triglycerides,leukocyte count of peritoneal fluid for the first time.Logistic regression analysis identified an increased likelihood of frequent PD-related peritonitis with high BMI,severe hypertension,low hemoglobin and low serum albumin.Conclusions Malnutrition,high BMI,and severe hypertension are risk factors of frequent PD-related peritonitis.Measures to improve anemia and hypoproteinemia,control blood pressure and maintain standard weight,and positive and regular treatment of peritoneal endogenous infection may contribute to the prevention and control of the frequent PD-related peritonitis.